POPULAR CULTURE AND YOUTH EDUCATION - Tulanov Mamasidiq (Web of Journals Publishing, 2024)
Nowadays, the negative influence of “mass culture” is increasing, as it negatively affects the national spirituality and worldview of young people. “Popular culture” causes many people in the world to subconsciously enter the virtual world of the “abstract world”. Observers, researchers and scientists estimate that today 10 percent of the world's population has entered the virtual world. In other words, you are exposed to internet surveillance. 70 percent of them are men.Researchers divide those addicted to the Internet into five groups: 1) virtual acquaintances; 2) cybersex or pornography users; 3) those who gamble on the Internet; 4) online gamers; 5) Those who “enjoy” surfing the Internet or open websites without thinking about a purpose.